Seven infectious bronchitis virus genotypes including South American-origin G1-11 and Asian-origin GVI-1 circulated in southern African poultry from 2010 to 2020 - Christine Strydom; Celia Abolnik (Virus Research)
Infectious bronchitis virus (IBV) affects the respiratory, urogenital and reproductive systems of chickens and causes major economic losses. Biosecurity and vaccinations are used to limit the disease's impact, and identifying the circulating strains is important for selecting appropriate vaccines. The partial spike (S1) genes of 364 IBVs, isolated from commercial chickens in Botswana, Eswatini, Namibia and South Africa from 2010 to 2020, were phylogenetically analyzed. Seven genotypes were identified: 184 viruses (50,5 %) were classified as genotype GI-19 (QX) and 78 (21,4 %) were GI-1 (Mass/H120). Thirty-nine (10,7 %) were genotype GI-13 (4/91), 29 (8,0 %) were GVI-1 (TC07–2), 19 (5,2 %) were GI-23 (Variant 2), and 13 (3,6 %) were GI-11 (UFMG/G-Brazil). Two (0.5 %) viruses belonged to the GIV-1 (DE/072/92) genotype. Genotype GI-11 had not been reported outside South America before but has evidently circulated in South Africa for at least a decade. Similarly, genotype GVI-1, previously thought to be restricted to Asia, has been present in southern Africa since at least 2010. Prior to 2013, only Mass and H120 vaccines were permitted to be used in South Africa, but since 2013 793/B (GI-13), QX (GI-19), 4–91 (GI-13) and Variant 2 (GI-23) live attenuated vaccines were permitted. Accordingly, the four IBV variants we identified were putative recombinants of genotypes G1–1 and G1–19, G1–13 and G1–19, or G1–13 and unknown IBV strains, but these variant viruses did not spread extensively or persist in the region. The phylogenetic evidence points to imported contaminated poultry and poultry products as the source of new IBV genotypes in southern Africa.